need to simplify
(-2p)^{4} is same as: (-2p)(-2p)(-2p)(-2p) --> (-2)^{4 }*p^{4 }--->16p^{4}
need to simplify
(-2p)^{4} is same as: (-2p)(-2p)(-2p)(-2p) --> (-2)^{4 }*p^{4 }--->16p^{4}
You have a multiplication, raised to a power.
So, there's a theory that says:
(a*b)^c = (a^c)*(b^c)
- this can be proven by expanding and rearranging the order of the multiplications. As an example:
(2*3)^4 = (2*3)*(2*3)*(2*3)*(2*3) = (2*2*2*2)*(3*3*3*3) = (2^4)*(3^4) = 16*81...
Further, if you do not have a value for your variable, then you can't compute a simpler expression that combines the variable with the power - once you get down to p^4, that's as simple as that part of the expression will get.